Analisis Implementasi E-Musrenbang Terhadap Perencanaan Pembangunan di Kota Surabaya dengan Pendekatan Problem Tree Analysis - Bella Nofita Ramadani; Rachel Amanda Delia; M. Noer Falaq Al Amin (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
Development planning is one of the important processes to improve the welfare of people in a region. In addition to issuing decentralization and regional autonomy policies to accelerate regional development and decision-making, the government also issued a Musrenbang program, which is now adapted to the progress of time to develop into E-Musrenbang. E-Musrenbang was created to overcome the problems in the conventional musrenbang system. Surabaya City is one of the cities that have successfully implemented E-Musrenbang, but in its implementation there are still gaps to be improved. The purpose of this study is to analyze the level of participation of the Surabaya community in the E-Musrenbang program. This research uses literature review and problem tree analysis methods. The results of this study focus on analyzing the problems that cause the low level of participation of the Surabaya community in several areas.  Some of the problems include the lack of socialization and education about the E-Musrenbang program, not all people have access to the Internet, the E-Musrenbang system is considered complicated and difficult to use by most ordinary people, and finally the lack of public trust in the government.